3-D multicomponent full waveform inversion for shallow-seismic target: Ettlingen Line case study. Issue 2 (17th December 2021) - Irnaka, T M; Brossier, R; Métivier, L; Bohlen, T; Pan, Y
SUMMARY: In this work, we investigate methodological development and application of viscoelastic full waveform inversion to a multicomponent source and receiver data set at the near-surface scale. The target is located in Germany and lies in an ancient war trench from the War of the Spanish Succession that was buried at approximately 1 m depth. We present the pre-processing of the data, including a matching filter correction to compensate for different source and receiver coupling conditions during the acquisition, as well as a dedicated multistep workflow for the reconstruction of both P -wave and S -wave velocities. Our implementation is based on viscoelastic modelling using a spectral element discretization to accurately account for the wave propagation complexity in this shallow region. We illustrate the inversion stability by starting from different initial models, either based on dispersion curve analysis or homogeneous models consistent with first arrivals. We recover similar results in both cases. We also illustrate the importance of accounting for the attenuation by comparing elastic and viscoelastic results. The 3-D results make it possible to recover and locate the trench precisely in terms of interpretation. They also exhibit another trench structure, in a direction forming an angle at 45° with the direction of the targeted trench. This new structure had been previously interpreted as an artifact in former 2-D inversion results. The archaeological interpretation of this new structure is still a matter of discussion.